2006
DOI: 10.1002/eat.20292
|View full text |Cite
|
Sign up to set email alerts
|

Experimental test of the affect‐regulation theory of bulimic symptoms and substance use: A randomized trial

Abstract: Objective: Conduct a randomized trial to test whether a cognitive behavioral intervention designed to decrease depressive symptoms produces subsequent decreases in bulimic and substance use symptoms.Method: Female participants (N ¼ 145) with elevated depressive symptoms were randomly assigned to a 4-session depression intervention or a measurement-only condition and assessed through 6-month follow-up.Results: Relative to control participants, intervention participants showed decreases in depressive symptoms. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 72 publications
4
38
0
1
Order By: Relevance
“…It may be, for example, that binge eating pathology and the subjective experience of stress share an underlying cause, or that subtle prodromal symptoms of BED/ BN cause elevated levels of perceived stress. Nonetheless, in this regard it is of note that recent experimental work by Burton et al 22 has shown that interventions that achieve a decrease in negative affect have a salutary effect on bulimic symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…It may be, for example, that binge eating pathology and the subjective experience of stress share an underlying cause, or that subtle prodromal symptoms of BED/ BN cause elevated levels of perceived stress. Nonetheless, in this regard it is of note that recent experimental work by Burton et al 22 has shown that interventions that achieve a decrease in negative affect have a salutary effect on bulimic symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, one participant described how in response to others' negative views of eating disorders, she utilised eating disorder behaviour as a coping strategy; thus, contributing to maintaining the eating disorder and linking to research which suggests eating disorder behaviour can function as a potential coping mechanism for managing negative emotions (e.g. Burton, Stice, Bearman, & Rohde, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Well-established risk factors for EP more generally that are supported by multiple independent prospective studies include elevated perceived pressure to be thin, internalization of the thin-ideal standard of female beauty, body mass, body dissatisfaction, and negative affect [6], [7]. Randomized experiments reducing thin-ideal internalization, body dissatisfaction, and negative affect also resulted in reductions in ED symptoms [8], [9], suggesting that these may be causal risk factors. Dieting was previously thought to be a well-established risk-factor for EP because it predicted future EP in prospective studies [10].…”
mentioning
confidence: 99%